CASE STUDY ON THE OPTIMIZATION OF TURBOCHARGER PERFORMANCE TO IMPROVE THE PERFORMANCE AND COST EFFICIENCY OF A TWO-STROKE MAIN ENGINE ON THE MT. MABROUK - Eka Nurmala; Andi Muhammad Thoriq Hafiz; Thaibil Anwar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The turbocharger is a crucial component in diesel engines, operating by utilizing exhaust gases produced during combustion. These gases flow through the exhaust manifold and function to compress the intake air entering the cylinders, supporting both scavenging and combustion processes. This study aims to examine efforts to maintain turbocharger performance in relation to the efficiency of the main engine. Data were collected onboard MT. Mabrouk from November 4, 2024, to July 7, 2025, by observing intake air pressure, turbocharger rotational speed, and exhaust manifold temperature, which were continuously monitored and recorded during testing. The findings indicate that proper turbocharger maintenance significantly increases engine output and fuel efficiency, with an average improvement of 18%. The researchers concluded that factors such as carbon deposits, clogged air filters, insufficient bearing lubrication, and elevated exhaust gas temperatures may lead to turbine imbalance, reduced combustion efficiency, slower vessel speed, increased fuel consumption, and shortened component lifespan. Preventive maintenance including turbine cleaning, turbo oil replacement, and optimization of the cooling system proved effective in improving turbocharger efficiency and overall engine performance.